Correction: The effect of M. tuberculosis lineage on clinical phenotype. - Duc Hong Du; Ronald B Geskus; Yanlin Zhao; Luigi Ruffo Codecasa; Daniela Maria Cirillo; Reinout van Crevel; Dyshelly Nurkartika Pascapurnama; Lidya Chaidir; Stefan Niemann; Roland Diel; Shaheed Vally Omar; Louis Grandjean; et al. (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001788.].